2020
DOI: 10.1016/j.rbms.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Where has the quest for conception taken us? Lessons from anthropology and sociology

Abstract: Louise Brown, the world's first test-tube baby, was born more than 40 years ago in England. For Louise Brown's infertile mother, Lesley, in-vitro fertilization (IVF) was the 'hope technology' which allowed her to overcome her tubal infertility after 9 years of heartbreaking involuntary childlessness. Since then, IVF has travelled to diverse global locations, where millions of individuals and couples have embarked on technologically assisted 'quests for conception'. After 40 years of IVF, where has the quest fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 78 publications
0
25
0
1
Order By: Relevance
“…Pronatalist religious pressures to pursue egg freezing appear to be emerging in other contexts as well, as shown for some Muslim and observant Christian women (Inhorn et al 2020). Thus, future studies of egg freezing must be conducted in multiple national and religious contexts to assess how religious moralities and community-based social pressures factor into single women's "quests for conception" through egg freezing (Inhorn 2020). Such studies will also contribute to the rich anthropological scholarship on the symbolic importance and value of eggs to women's reproduction, begun by Emily Martin (1987Martin ( , 1991 and carried forward by anthropologists working in numerous global settings (see Inhorn andInhorn 2020 for overviews).…”
Section: Discussionmentioning
confidence: 99%
“…Pronatalist religious pressures to pursue egg freezing appear to be emerging in other contexts as well, as shown for some Muslim and observant Christian women (Inhorn et al 2020). Thus, future studies of egg freezing must be conducted in multiple national and religious contexts to assess how religious moralities and community-based social pressures factor into single women's "quests for conception" through egg freezing (Inhorn 2020). Such studies will also contribute to the rich anthropological scholarship on the symbolic importance and value of eggs to women's reproduction, begun by Emily Martin (1987Martin ( , 1991 and carried forward by anthropologists working in numerous global settings (see Inhorn andInhorn 2020 for overviews).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey showed that almost all infertility physicians identified cost as the largest barrier to care and, unsurprisingly, this translated into a stratification of (assisted) reproduction across familiar lines of race- and class-based social hierarchies ( McLaughlin et al, 2018 ). The average cost for a US IVF cycle is approximately four times the global average, and currently amounts to around $23,474 ( FertilityIQ., 2020b , Inhorn, 2020 ). As of April 2021, only 19 of 51 states require some form of insurance coverage for infertility treatment, and only 11 states have laws for coverage of fertility preservation for medically induced infertility ( Resolve, 2021 ).…”
Section: Fertility Benefits and The Contested Demand For Proactive Fe...mentioning
confidence: 99%
“…chemotherapy). In the USA, the vast majority of people undergoing IVF or egg freezing pay out of pocket ( Inhorn, 2020 , Mohapatra, 2014 ). However, even those women who do have health insurance find that they still have significant out-of-pocket expenses for egg freezing after a serious diagnosis.…”
Section: Fertility Benefits and The Contested Demand For Proactive Fe...mentioning
confidence: 99%
“…Тем не менее применение донорского материала в репродукции человека остается одной из самых спорных репродуктивных тех нологий [Beeson, Darnovsky, Lippman, 2015]. Как и многие аспекты исследований в науках о жизни (например, исследования и использование стволовых клеток, исследования генома человека и манипуляция генами) использование репро дуктивных технологий затрагивает основы миропонимания и самопонимания человека, поэтому вызывает неприятие и враждебность со стороны разного рода традиционалистов [Forman Rabinovic, Sommer, 2018;Mathieu, 2020], а также боль шое количество споров о юридической субъектности, правах, равенстве и дру гих политико правовых проблемах [Inhorn, 2020;Ferraretti et al, 2010;Merchant, 2020]. Таким образом, отношение общества к репродуктивному донорству требует, на наш взгляд, более детального изучения.…”
Section: семья и демографияunclassified